Mediterranean Recluse Spider, Loxosceles rufescens (Araneae: Sicariidae) from Charkhab Cave, Southern Iran - Saber Sadeghi; Meysam Dashan; Mohammad Javad Malek-Hosseini (Tehran University of Medical Sciences, 2017)
Background: The best-known dangerous spiders belong to the six genera. The genus Loxosceles or violin spiders are well known for their ability to cause skin necrosis or loxoscelism. All Loxosceles species have medical importance due to their necrotizing venom. The present article reports the occurrence of L. rufescens in Charkhab Cave, south of Iran (Larestan). Methods: The specimens were collected from the Charkhab Cave using handling forceps, paintbrush and aspirator and preserved in 96% ethanol. Results: Loxosceles rufescens, a medically important spider, is recorded from Charkhab Cave in Fars Province (southwest of Iran). Identification of L. rufescens was performed based on external morphology and the features of male genitalia. Conclusion: Presence of L. rufescens in south of Iran especially in a cave confirmed that this species is a widely distributed species in Iran. Therefore, cavers or cave visitors should be aware of this poisonous spider in caves.